A Look Behind the Scenes - Claus Frederik Sørensen (Acta Periodica Duellatorum, 2016)
From the 4th – 7th of July 2016, the annual International Medieval Congress was held in Leeds, England. Among the many different sessions two specifically addressed historical European martial arts. The first session discussed and commented upon modern practices and interpretations of historical European martial arts, each paper being based on good practice and the proper criteria for academic research. The second session, in which this paper was presented, went more “behind the scenes”, discussing the importance of thorough analysis of the historical context which remains essential to forming a foundation for solid hypotheses and interpretations.